2017
DOI: 10.20448/journal.504.2017.41.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Characterization of Salmonella Isolates from Poultry Farms in Ilorin, Nigeria

Abstract: Poultry birds are very important source of essential proteins in developing countries, but also play an important role in transmission of Salmonella to human and nonhuman. Exposure to this pathogen also occurs through use of poultry droppings as manure for crop and vegetable production. This study investigated prevalence of Salmonella in feces of poultry farms in Ilorin, Nigeria. Salmonella isolated were further characterized by molecular method. Fecal samples were cultured in pre-enrichment medium, Selenite F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…We reported a 21.4% prevalence of Salmonella in commercial poultry in Ibadan. Previous studies have reported the prevalence of Salmonella infection in poultry farms and chickens in Nigeria to be between 2.0% and 43.0%, 17 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 and this is similar to the prevalence reported in another study conducted in Bangladesh. 33 Salmonella have been implicated in bacteraemia, septicaemia and gastroenteriti s in humans, and their presence in poultry chickens may pose serious health risks to humans.…”
Section: Discussionsupporting
confidence: 85%
“…We reported a 21.4% prevalence of Salmonella in commercial poultry in Ibadan. Previous studies have reported the prevalence of Salmonella infection in poultry farms and chickens in Nigeria to be between 2.0% and 43.0%, 17 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 and this is similar to the prevalence reported in another study conducted in Bangladesh. 33 Salmonella have been implicated in bacteraemia, septicaemia and gastroenteriti s in humans, and their presence in poultry chickens may pose serious health risks to humans.…”
Section: Discussionsupporting
confidence: 85%
“…In Nigeria, Salmonella Typhi in raw beef (Orji et al 2004), in environmental samples and vegetables, irrigated with wastewater from abattoir sources (Abakpa et al 2015) has been reported. Its associate , S. Paratyphi, had been found from poultry and meat (Orji et al 2004; Ogunleye et al 2006; Babatunde et al 2017) and elsewhere by Bertelloni et al (2017). With typhoidal Salmonellosis endemic (Akinyemi and Fakorede, 2018; Fashae et al 2010; Smith et al 2016; Adikwu et al 2018), this is the first detection and report of Salmonella Typhi, a known human host‐adapted pathogen from poultry droppings in Nigeria.…”
Section: Discussionmentioning
confidence: 92%